Exploring the Prevalence and Correlates of Substance Abuse Amongst the Adolescents of Dharan, Eastern Nepal - Chapagain, Kumud; Rai, Dillisher; Koirala, Bhawesh; Rauniyar, Gajendra Prasad (Journal of Nepal Health Research Council, 2020)
Background: The burden of substance abuse amongst the youths has increased worldwide including Nepal. There is limited data on prevalence of substance abuse among the adolescents. Hence this study aims to determine the prevalence of substance abuse amongst the adolescents of Dharan, Eastern Nepal. Methods: A cross-sectional study was conducted from July 2018 to December 2018. Self-administered structured questionnaire adapted from National Youth Survey sponsored by the Centre for Substance Abuse Prevention was used for data collection from 1125 higher secondary school students. Data was cleaned in Microsoft Excel and analysed using SPSS version 11.5. Results: Prevalence of ever users of tobacco were 46.04% of which the current users were 20.46%, ever users of alcohol were 37.58% of which 15.20% were current users and ever users of drug was 18.19% of which 18.13% were current users. The average age of initiating tobacco, alcohol and drugs were 14.21 ± 3.51, 15.13 ± 7.43 and 14.32 ± 4.41 years respectively. More than half of the drug users (50.71%) used cannabis and the most common reason for using any substance was peer pressure (91.64%). More than one-third (39.5%) purchased any of these substance from local shops. Conclusions: The study reported significant proportion of adolescents involved in substance abuse. The findings of this study may be beneficial for revising/ updating action plans on prevention and control of substance abuse in Nepal. Keywords: Adolescents; alcohol; drug; substance abuse; tobacco.